2015
DOI: 10.1007/s11096-015-0146-8
|View full text |Cite
|
Sign up to set email alerts
|

Potential drug-related problems detected by electronic expert support system: physicians’ views on clinical relevance

Abstract: In most patients with multi-dose drug dispensing, EES detected potential drug-related problems, with the majority of the alerts regarded as clinically relevant and some followed by measurable changes in drug treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 45 publications
2
27
1
Order By: Relevance
“…Some of the alerts may already have been resolved or evaluated by the healthcare services without the pharmacists knowing about this, and there is a risk that patients receive contradicting information from the pharmacist. A previous study among physicians showed that they regarded 68% of EES alerts to be clinically relevant, and 11% of all alerts were followed by a change in drug treatment [ 26 ]. In our study, contact with the prescriber and change of prescription was documented for only 0.2% of all closed alerts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the alerts may already have been resolved or evaluated by the healthcare services without the pharmacists knowing about this, and there is a risk that patients receive contradicting information from the pharmacist. A previous study among physicians showed that they regarded 68% of EES alerts to be clinically relevant, and 11% of all alerts were followed by a change in drug treatment [ 26 ]. In our study, contact with the prescriber and change of prescription was documented for only 0.2% of all closed alerts.…”
Section: Discussionmentioning
confidence: 99%
“…EES is not available to prescribers in Swedish health care. Previous studies have described the potential DRPs detected by EES in patients with multi-dose drug dispensing and have shown that physicians regard the majority of alerts as clinically relevant [ 25 , 26 ]. Although EES has been available at pharmacies for many years, its use has been low and only studied in a few small studies where most of them are not published scientifically [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, as previously described this limitation reflects the working methods used by clinical pharmacists in Norway at the time, in which medicines reconciliation was not included. (155,195).…”
Section: Discussion Of Methodologymentioning
confidence: 99%
“…17 Several systems have been proposed for the classification of DRP, with the Pharmaceutical Care Network Europe (PCNE) being one of the most commonly used classification systems in hospital practice. 18 Several DRP detection strategies have been developed, including pharmacist review of medication orders (MO), the use of computerised physician order entry (CPOE) systems couple with clinical decision support programs [19][20][21] that allow the clinical pharmacist to have an active participation within the healthcare team. 5 8 22-24 However, despite the clinical and economic relevance of DRP, very few studies have investigated the incidence, types and causes of DRP in patients hospitalised in general medical and surgical wards.…”
Section: Introductionmentioning
confidence: 99%